From Grindal to Whitgift - Pierre Kapitaniak (Etudes Epistémè)
Reginald Scot’s The Discoverie of Witchcraft is above all remembered for its proto-anthropological approach to the question of witchcraft, while the anti-Catholicism of his books is usually played down or rapidly acknowledged as part of a general trend. And yet the author fully participates in a vast campaign of anti-Catholic propaganda fuelled by the Jesuit missions of the early 1580s and further intensified by the appointment of John Whitgift as archbishop of Canterbury in 1583. Peter Elmer has recently demonstrated that Scot was charged by Whitgift with writing a report of non-conformist activities in Kent, which begs to re-examine The Discoverie of Witchcraft not only through the anti-Catholic prism but also through an anti-puritan one. Yet Scot’s treatise shows very few traces of such an important shift in the doctrinal positions of its author who, until the arrival of Whitgift, seemed to have shared Edmund Grindal’s views by supporting tolerance and freedom of preaching. The present paper will try to show that the answer may lie in the very circumstances of its composition, written between 1582 and 1584 and published in the summer of 1584.